Pemahaman Moderasi Beragama Dalam Menciptakan Kerukunan Antar Umat Beragama - Nuriyati, Tuti; Juliana Hafsah, Siti; Nurfatiha, Nurfatiha (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
Research on how to understand religious moderation in creating harmony in society where previously there were still some people who did not understand religious moderation. This research was conducted using a qualitative approach. This research is descriptive in nature. This study collects data through observation techniques, interviews and documentation review. The results of this study indicate that understanding religious moderation is very important to build or create inter-religious harmony because religious moderation is one of the main indicators as an effort to build culture and national character. Religious moderation can be used as a cultural strategy to care for an Indonesia that is peaceful, tolerant and respects diversity. Religious Moderation is a way of life to get along in harmony, respect, maintain and tolerate without having to cause conflict because of differences. By understanding and strengthening religious moderation, it is hoped that religious people can position themselves appropriately in a multi-religious society, so that social harmonization and balance in social life occur